More than sedum: Colonizing weedy species can provide equivalent green roof ecosystem services - Heim, Amy; Biermann, Bridget; Hicks, Taylor; Buffam, Ishi; Lundholm, Jeremy (Nature-based solutions, 2024)
Green roofs are typically constructed for their provision of both environmental and associated economic benefits including increased habitat, thermal regulation, mitigation of air and noise pollution, and stormwater retention. The provision of these various ecosystem services is sharply influenced by plant species composition, with particular species and traits known to excel at specific services. For this reason, increased biodiversity can improve the overall provision of ecosystem services. However, one key contributor to green roof biodiversity, colonizing species, is understudied. In this study we examine the contribution of common colonizing species (lawn weeds) and one green roof species, to three important ecosystem services: stormwater retention, temperature reduction, and nitrogen retention. This experiment used replicated green roof modules to examine 13 different treatments: eight colonizing species in monoculture, one green roof species monoculture, two treatments with a mix of colonizing species, one treatment where vegetation was allowed to spontaneously colonize, and one substrate only control. Results from this study show that mixtures of colonizing species performed well for all three monitored ecosystem services, with a few of the monocultures, especially those with high biomass or canopy density, performing similarly. While it is unlikely that green roof installations would proceed equally well without adding vegetation, our results indicate that colonizing species can support a viable green roof ecosystem. This study shows that spontaneous growth and/or allowing new species to colonize may be a viable design alternative for green roofs, decreasing cost while maintaining the desired ecosystem services.